2021
DOI: 10.21930/rcta.vol22_num1_art:1892
|View full text |Cite
|
Sign up to set email alerts
|

Tendencia genética y fenotípica de la producción de leche: caso de un establo comercial del valle de Huaura, Perú

Abstract: El objetivo de esta investigación fue determinar la tendencia genética y fenotípica de la producción de leche (PL) de vacas Holstein de un establo del valle de Huaura, Perú. Se evaluaron 2.590 hembras (vacas y terneras) para el cálculo de los valores genéticos estimados (VGE) y 2.862 lactaciones estandarizadas a 305 días y dos ordeños diarios, del primer al quinto parto de 1.892 vacas del periodo 1999-2017, mediante un modelo animal de medidas repetidas. Con el software ASReml, se estimó una heredabilidad (h2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The present GT for MY in the years of study, being -1.39 kg/year was close to − 2.46 kg/year (Şahin et al,2012;Vasquez et al,2021) and is in agreement with the results of Effa et al (2011) and Shalan et al (2022), who revealed that a negative GT of milk production traits occurred under the tropical conditions. However, Hossein-Zadeh (2011), Chegini et al (2013), Haiduck et al (2019) and Abou Saq and Ben Naser (2021) reported significant (p<0.0001) positive estimates of GT, ranging from +4.15 to +21 kg/year for MY which probably as a result of selecting bulls with high genetic value.…”
Section: Genetic Trend Of Milk Yieldsupporting
confidence: 91%
See 2 more Smart Citations
“…The present GT for MY in the years of study, being -1.39 kg/year was close to − 2.46 kg/year (Şahin et al,2012;Vasquez et al,2021) and is in agreement with the results of Effa et al (2011) and Shalan et al (2022), who revealed that a negative GT of milk production traits occurred under the tropical conditions. However, Hossein-Zadeh (2011), Chegini et al (2013), Haiduck et al (2019) and Abou Saq and Ben Naser (2021) reported significant (p<0.0001) positive estimates of GT, ranging from +4.15 to +21 kg/year for MY which probably as a result of selecting bulls with high genetic value.…”
Section: Genetic Trend Of Milk Yieldsupporting
confidence: 91%
“…,El- Awady et al (2017),Öztürk et al (2021) andShalan et al (2022), and higher than the range of 0.14 -0.18 stated by Faid Allah (2015),Vasquez et al (2021) andPangmao et al (2022). The current low h 2 estimate of MY relative to some of those reported above may indicate a small additive genetic variance and/or high residual variance, which suggests that this trait was highly affected by some environmental factors such as farm, feed, management and climatic changes.…”
mentioning
confidence: 65%
See 1 more Smart Citation